Pemodelan Markov Switching Autoregressive (MSAR) pada Data Kurs Rupiah terhadap Dollar Amerika - Muh. Fahmi Nur Akbar; Nusar Hajarisman (UNISBA Press, 2024)
Abstract. Linear models such as Autoregressive (AR), Moving Average (MA), and Autoregressive Integrated Moving Average (ARIMA) are commonly used for time series data where there is a linear relationship between the current data and past data. However, these models are not capable of explaining structural changes in economic variables caused by crises. Therefore, an analytical method that can analyze time series data on economic and financial variables experiencing regime switching is introduced. The method used to model time series data on economic and financial variables experiencing regime switching is the Markov Switching Autoregressive (MSAR) model. This method was applied to data on the Rupiah to U.S. Dollar exchange rate from January 1 to December 31, 2023. The objectives of this study are to develop the MSAR model, determine the transition probabilities of each state, assess the average duration of each state, and forecast the Rupiah to U.S. Dollar exchange rate. The MS(2)AR(2) model was chosen as the best model because it had the lowest Akaike’s Information Criterion (AIC) value of 2553.927. The Mean Absolute Percentage Error (MAPE) of 27.91% indicates reasonably good forecasting accuracy. Based on this model, the Rupiah exchange rate tends to stay in an increasing condition for about 9 periods and in a decreasing condition for about 2 periods. Abstrak. Pemodelan linear seperti model Autoregressive (AR), model Moving Average (MA), dan model Autoregressive Integrated Moving Average (ARIMA) digunakan untuk data runtun waktu yang terdapat hubungan linear antara data sekarang dan data masa lalu. Namun, model tersebut belum mampu menjelaskan adanya perubahan struktur pada peubah-peubah ekonomi yang disebabkan olehkrisis. Oleh karena itu, perkenalkan metode analisis yang dapat menganalisis data runtun waktu pada peubah-peubah ekonomi dan keuangan yang mengalami perubahan kondisi (regime switching). Metode yang digunakan untuk memodelkan data runtun waktu pada peubah ekonomi dan keuangan yang mengalami perubahankondisi adalah pemodelan Markov switching autoregreassive (MSAR). Metode ini diterapkan pada data Kurs Rupiah terhadap Dollar Amerika pada tanggal 1 Januari - 31 Desember 2023. Adapun tujuan dari penelitian ini adalah membentuk model MSAR, mengetahui nilai peluang transisi setiap state, mengetahui rata-rata lama durasi state dan peramalan pada data kurs Rupiah terhadap Dollar Amerika. Model MS(2)AR(2) dipilih sebagai yang terbaik karena memiliki nilai Akaike’s Information Criterion (AIC) terkecil, yaitu 2553.927. Nilai Mean Absolute Percentage Error (MAPE) sebesar 27.91% menunjukkan akurasi peramalan yang cukup baik.Berdasarkan model ini, kurs Rupiah cenderung bertahan dalam kondisi peningkatan selama 9 periode dan dalam kondisi penurunan selama 2 periode